Three-Years Outcome of Microdiscectomy via Paramedian Approach for Lumbar Foraminal or Extraforaminal Disc Herniations in Elderly Patients over 65 Years Old - Yeo, Chang Gi; Jeon, Ikchan; Kim, Sang Woo; Ko, Sam Kyu; Woo, Byung Kil; Song, Kwang Chul (Korean Journal of Spine, 2016)
Lumbar foraminal or extraforaminal disc herniations (FEFDH) have unusual clinical features and higher incidence in elderly patients compared to usual intraspinal canal disc herniations. We evaluated the efficacy of microdiscectomy via paramedian approach for lumbar FEFDH in elderly patients over the age of 65. Retrospective study was performed in 68 patients over the age of 65 (23 male and 45 female patients; 71.46±3.87 years) who underwent microdiscectomy via paramedian approach for unilateral lumbar FEFDH causing sciatica. The radiological factors including degree of slippage, presence of instability, disc height, and degree of disc degeneration; pain and functional status by the means of visual analogue scale score, Oswestry Disability Index score, and Macnab classification were analyzed preoperatively and during the postoperative follow-up period of 3 years to evaluate the efficacy of the surgical treatment. Pain and functional status improved according to short- and long-term follow-up evaluations after surgery. Radiological changes following surgery, which can be understood as structural deteriorations and deformations, did not represent patient condition. Nine patients underwent additional surgery due to sustained or recurring leg pain of aggravation of back pain, and fusion surgery was required for 3 patients. Degree of preoperative slippage was the only statistically significant factor related to additional surgery (p<0.05). Microdiscectomy via paramedian approach for FEFDH may be a good surgical alternative in elderly patients. Radiological changes after surgery did not show a concordance with patients' actual functional status. The excessive preoperative slippage tended to lead to unfavorable result after surgery and was associated with additional surgery.